Quantização de teoria de Cordas Bosônicas - Gonçalves, Julia Carolina (Universidade Federal de São Carlos, 2025)
Developed in 1969, String Theory was formulated aiming to explain the strong interactions. However, throughout its development, it was noticed that the theory has the potential to become an unification model for the 4 fundamental interactions of nature. While keeping the usual patterns of quantization together with general covariance’s standard kinematics, its only new axiom is that, in a fundamental level, the matter is composed of unidimentional objects: the strings. Despite of its simplicity, the String Theory is currently the main proposal for the unification of Quantum Gravity and QFT. Thereby, the study of this field of knowledge has na unquestionable importance, not only in the matter of High Energy Physics but also in mathematics and in understanding the Universe itself and its functioning. Therefore, the objective of this monograph is to present two approaches to the quantization of string theory, alongside a discussion on gauge theory and conformal field theory.
Quantization of Bosonic String Theory
Keywords: Teoria de Cordas; Física teórica; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA DAS PARTICULAS ELEMENTARES E CAMPOS::TEORIA GERAL DE PARTICULAS E CAMPOS